The Characteristics of Seismic Response on Hard Interlayer Sites - Jie Su; Zhenghua Zhou; You Zhou; Xiaojun Li; Qing Dong; Yafei Wang; Yuping Li; Liu Chen (Advances in Civil Engineering)
Based on the engineering geological data of a nuclear power plant site, nine engineering geological profiles were created with hard interlayers of different thicknesses. The equivalent linearization method of seismic motion segment-input used for one-dimensional nonlinear seismic response analysis was applied to study the effect of the interlayer thickness on the peak acceleration and the acceleration response spectra of the site seismic response. The results showed that there was an obvious influence of hard interlayer thickness on site seismic responses. With the increase of hard interlayer thickness, the site nonlinear effect on seismic responses decreased. Under the same thickness of the hard interlayer, the nonlinear effect of the site was strengthened with the higher input peak acceleration. In addition, the short-period acceleration response spectrum was found to be significantly influenced by the hard interlayer and showed that the longer the period, the less influence of the hard interlayer on the acceleration response spectrum coordinates. Moreover, the influenced frequency band was wider with the increase in the thickness of hard interlayer.